Pendekatan Fenomenologi Husserl dan Kontribusinya bagi Pengembangan Dakwah di Indonesia - Alnashr, M Sofyan (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2024)
Religious practices and community social interactions give birth to many events that have different meanings for each person. Revealing the hidden meaning of an event, especially from the perspective of the person experiencing it, can be done with a phenomenological approach. The purpose of this research is to explain the contribution of Husserl's phenomenological approach to the development of Islamic da'wah.. This research is a literature research on Husserl's phenomenological concept and how to apply it in da'wah. Data were collected from various documents related to the main topic, both from print and electronic sources. Miles & Huberman's qualitative interactive analysis was used to analyze the data through the stages of data presentation, data reduction, and conclusion drawing. The results showed that basically phenomenological studies attempt to find the meaning or value of a phenomenon with two main things in focus, namely textural description and structural description. Textural description is about what is experienced, while structural description is related to how the context influences the subject in experiencing and interpreting the phenomenon. Husserl's phenomenological approach is one of the right approaches in examining social and religious phenomena and then conveying the content of da'wah in accordance with existing phenomena in the perspective of Islamic teachings so as to provide a holistic understanding of the phenomenon.